CCENT ICND1 100-105 Exam Cram - Sequeira, Anthony (Exam cram., 2016)
I>CCENT ICND1 100 -105 Exam Cram is the perfect study guide to help you pass the 100-105 ICND1 exam, providing coverage and practice questions for every exam topic. The book contains an extensive set of preparation tools, including topic overviews, exam alerts, Cram Savers, Cram Quizzes, chapter-ending review questions, author notes and tips, and an extensive glossary. The book also contains the extremely useful Cram Sheet tear-out: a collection of essential facts in an easy to review format. Complementing all these great study tools is the powerful Pearson Test Prep practice test software, complete with hundreds of exam-realistic practice questions. This assessment software offers you a wealth of customization options and reporting features, allowing you to test your knowledge in study mode, practice exam mode, or flash card mode. Covers the critical information you'll need to know to score higher on your CCENT exam! Compare and contrast networking models including OSI and TCP/IP Compare and contrast various networking technologies and architectures Apply troubleshooting methodologies Master subnetting in IPv4 Understand important details of IPv6 Describe and verify key switching topics Configure Layer 2 switches, including Port Security Configure and verify Inter-VLAN routing Configure and verify routing Configure and verify key infrastructure services including DNS, DHCP, DHCP, NTP, and NAT Configure and verify infrastructure maintenance Configure Cisco device hardening Troubleshoot networks using key IOS tools This eBook edition of the CCENT ICND1 100-105 Exam Cram does not include the practice exams that come with the print edition. CENT ICND1 100 -105 Exam Cram is the perfect study guide to help you pass the 100-105 ICND1 exam, providing coverage and practice questions for every exam topic. The book contains an extensive set of preparation tools, including topic overviews, exam alerts, Cram Savers, Cram Quizzes, chapter-ending review questions, author notes and tips, and an extensive glossary. The book also contains the extremely useful Cram Sheet tear-out: a collection of essential facts in an easy to review format. Complementing all these great study tools is the powerful Pearson Test Prep practice test software, complete with hundreds of exam-realistic practice questions. This assessment software offers you a wealth of customization options and reporting features, allowing you to test your knowledge in study mode, practice exam mode, o ...